Suicide prevention gatekeeper training for those supporting refugees and asylum seekers: perspectives of participants. (2nd September 2021) - Posselt, Miriam; Loughhead, Mark; Ferguson, Monika; McIntyre, Heather; Kenny, Mary Anne; Procter, Nicholas
ABSTRACT: This research explored participants' experience and perceptions of a two-day suicide prevention education programme, and any impact that it has had on them and their work with refugees and asylum seekers since. At approximately six months post-training (May to September 2018), semi-structured telephone interviews were conducted with 15 participants. The interviews were audio-recorded, transcribed, and thematically analysed. Thematic analysis of the data identified two overarching themes and five subthemes. The two overarching themes were: (1) Changes to the individual and their practice; and (2) The culture and context of the work. Participants described a range of impacts that the training had on them and their workplace, in both personal and professional domains. The study findings suggest that equipping workers with skills and knowledge in culturally tailored and evidence-based suicide prevention can lead to an increased sense of hope, optimism, confidence, and agency and reportedly enabled workers to more readily intervene when presented with clients directly or indirectly communicating suicidal ideation. Findings support existing literature regarding gatekeeper training effectiveness. However, given the unique context of asylum seeker and refugee suicide, they also extend our understanding of the impact of bespoke or tailored approaches to gatekeeper training.